2020
DOI: 10.1088/1755-1315/421/6/062030
|View full text |Cite
|
Sign up to set email alerts
|

Modern technologies for using fish wastes in the production of collagen hydrolysates and functional beverages

Abstract: The research is devoted to the use of a cod skin hydrolysate as a component of citrus fruit beverages. It is demonstrated that the addition of a hydrolysate increases the content of protein in the beverage, slightly increases the viscosity of the beverage, and does not adversely affect its sensory characteristics. Hydrolysate is produced by enzymatic treatment of cod skin. The processing parameters allowing achieving the desired degree of destruction are determined. Physico-chemical parameters and sensory anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Increase in collagen synthesis and improvement in protein folding [176] Sparkling water Gelatin (skin, scales and fins) Antibacterial properties and antioxidant activity against superoxide and the DPPH radical [169] Fruit juice Hydrolysate collagen (cod skin) Good nutritional and physicochemical properties [165] Apple juice and djulis extract Collagen (green caviar) Improved skin moisture and elasticity [171] Apple juice Collagen (fish) Improved skin hydration, brightness, texture [175] Non-alcoholic rose-apple beverage Collagen (fish) Antioxidant properties [170] Dairy beverage Collagen (fish skin)…”
Section: Type Of Beverage Waste Food Ingredient Functionality Referencementioning
confidence: 99%
See 2 more Smart Citations
“…Increase in collagen synthesis and improvement in protein folding [176] Sparkling water Gelatin (skin, scales and fins) Antibacterial properties and antioxidant activity against superoxide and the DPPH radical [169] Fruit juice Hydrolysate collagen (cod skin) Good nutritional and physicochemical properties [165] Apple juice and djulis extract Collagen (green caviar) Improved skin moisture and elasticity [171] Apple juice Collagen (fish) Improved skin hydration, brightness, texture [175] Non-alcoholic rose-apple beverage Collagen (fish) Antioxidant properties [170] Dairy beverage Collagen (fish skin)…”
Section: Type Of Beverage Waste Food Ingredient Functionality Referencementioning
confidence: 99%
“…Additionally, approximately 22% of its content is made up of the fatty acids palmitic acid and oleic acid. FW is an important source of by-products (proteins and amino acids, collagen and gelatin, oil and several enzymes) used in several fields and the food industry a functional ingredients [ 164 , 165 , 166 , 167 ]. Some studies have demonstrated the use of by-products obtained from FW in beverages with functional properties such as antioxidants against superoxide, ABTS and DPPH radicals and antimicrobial activity [ 168 , 169 , 170 ].…”
Section: Food Waste As An Ingredient For the Preparation Of Functiona...mentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of biologically active substances to functional drinks is one of the ways to achieve their fast intestinal absorption. The drinks may be supplemented with flavoring ingredients and enriched with functional components, including collagen hydrolysate for connective tissue regeneration [18,19]. Isotonic drinks are of great biomedical interest because they are developed for normalization of water and electrolyte content in the body and correction of imbalance of minor nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Esses produtos geradosapresentam propriedades e utilidades variáveis, diferentes daquelas observadas nas moléculas nativas, assim, ao longo dos anos foram investigados hidrolisados de diferentes fontes como leveduras(MARSON et al, 2020), leite(AL-SHAMSI et al, 2018), resíduos lignocelulósicos (LI; QIWAN, 2020), carne suína(LI et al, 2020), carne de aves(WANG & SHAHIDI, 2018) e resíduos pesqueirosKRASNOVA;SEMENOV;ZARUBIN, 2020), sendo os últimos fontes promissoras de colágeno.A hidrólise do colágeno desintegra suas pontes de hidrogênio, o que resulta na conversão de sua estrutura nativa (tripla-hélice) em estruturas espirais "aleatórias". Esse produto pode ser fracionado ainda mais para obtenção de uma variedade de subunidades menores (Figura 3), com propriedades modificadas (menor viscosidade, baixo Ponto Isoelétrico, aumento da biodisponibilidade)(LEÓN-LÓPEZ et al, 2019;CHEN et al, 2014).…”
unclassified